Plyometric training`s effects on young male karatekas` jump, change of direction, and inter-limb asymmetry - Moreno-Azze, A.; Prad-Lucas, E.; Soñén, D. F.; de la Fuente, F. P.; Falcón-Miguel, D. (Sports, 2024)
This study analysed the effects of performing a plyometric training programme on different types of jumping and specific changes of direction, and their respective asymmetries in karatekas. Twenty male karatekas (age 19 ± 4 years) were distributed in two groups, the control group (CG) and the experimental group (EG). The EG group (n = 10) performed a 6-week intervention of unilateral plyometric training, performing countermovement jumps (CMJ), drop jumps (DJ), and long jumps (SH). The tests performed at the beginning and at the end of the intervention were a unilateral and bilateral countermovement jump test (CMJ), single-leg hop test (SH), single-leg side-hop test (SSH), triple hop test (TH), and change of direction in a karate position test (MKUKS). The EG group obtained improvements in the CMJ with the stronger (p = 0.01; ES = 0.39) and weaker leg (p = 0.01; ES = 0.59), in the SH with the weaker leg (p = 0.01; ES = 0.45), in the SSH with the weaker leg (p = 0.03; ES = 0.33), in the MKUKS (p = 0.00; ES = 0.98), and improved the asymmetries obtained in the TH (p = 0.02; ES = -0.85). The GC group obtained significant differences in the CMJ with the stronger (p = 0.03; ES = 0.46) and weaker leg (p = 0.00; ES = 0.69), in the bilateral CMJ (p = 0.02; ES = 0.24), in the SH with the weaker leg (p = 0.00; ES = 0.34), in the TH with the stronger (p = 0.00; ES = -0.15) and weaker leg (p = 0.01; ES = 0.09), and in the MKUKS test (p = 0.04; ES = -0.94). A between-group analysis showed improvements of the EG over the GC in the TH with the stronger leg (p = 0.02; ES = 1.05). Performing plyometric training provides improvements in jumping, mainly in horizontal jumps, reducing inter-limb asymmetries in repetitive jumps.